1986
DOI: 10.1038/jcbfm.1986.12
|View full text |Cite
|
Sign up to set email alerts
|

Normal Distribution of Regional Cerebral Blood Flow Measured by Dynamic Single-Photon Emission Tomography

Abstract: Summary: Regional CBF (rCBF) was measured quanti tatively using the inert-gas washout technique with xenon-133 and single-photon emission computed tomog raphy. Tomographic data were reconstructed by filtered back projection, and flow was calculated according to the double-integral method, Ninety-seven subjects ranging in age from 20 to 59 years received a single examination; eight of these received a second examination within 1 h of the first; seven others received a second examination separated from the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
67
3
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(86 citation statements)
references
References 32 publications
15
67
3
1
Order By: Relevance
“…Using the xenon-133 inhalation technique, Gur et al 30 and Shaw et al 31 observed significantly higher values in women than in men. In the subjects investigated by Devous et al, 21 females of different ages had higher hCBF and rCBF values than age-matched males; significant differences were found in the 20-29-and the 30-39-year-old groups. Yoshii et al 32 reported significantly higher CMRglu in young and elderly females than males.…”
Section: S Ismentioning
confidence: 85%
See 1 more Smart Citation
“…Using the xenon-133 inhalation technique, Gur et al 30 and Shaw et al 31 observed significantly higher values in women than in men. In the subjects investigated by Devous et al, 21 females of different ages had higher hCBF and rCBF values than age-matched males; significant differences were found in the 20-29-and the 30-39-year-old groups. Yoshii et al 32 reported significantly higher CMRglu in young and elderly females than males.…”
Section: S Ismentioning
confidence: 85%
“…20 Devous et al 21 found a mean±SD gray matter blood flow of 71 ±12 ml/100 g/min using xenon-133 SPECT. Our calculated mean (67-68 ml/100 g/min) and standard deviations of gray matter blood flow closely resemble those obtained with established three-dimensional techniques.…”
Section: S Ismentioning
confidence: 99%
“…Increased level of Glc spectra was detected in female orbital frontal cortex [115]. Functional brain imaging studies (single-photon emission tomography and positron emission tomography (PET)) indicate sex differences in brain metabolism, particularly in global and regional cerebral blood flow and glucose consumption [75,[118][119][120][121][122][123][124]. Cognitive activity resulted in increased flow of blood to the cerebral hemispheres.…”
Section: Biochemical Differencesmentioning
confidence: 99%
“…Finally, the T1-weighted structural images were spatially normalized and the same transformations were applied to the CBF maps. During this process, CBF maps got interpolated to a voxel size of 2 Â 2 Â 2 mm 3 . The normalized CBF maps were smoothed with an isotropic 12-mm full width at half-maximum Gaussian kernel to normalize the distribution of perfusion data as required within the framework of the subsequent statistical analyses and inference.…”
Section: Data Processingmentioning
confidence: 99%
“…However, its role in healthy ageing is not well understood. Early investigations of age-related CBF changes using positron emission tomography (PET) or single photon emission computed tomography (SPECT) found a general decline of CBF in whole brain or grey matter (GM) (3,4). More recent PET-based studies explored CBF in selected regions of interest (5,6) and stressed the confounding influence of partial volume effects (7,8) due to atrophy in the ageing brain.…”
mentioning
confidence: 99%